2018
DOI: 10.20944/preprints201803.0258.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Afamin and Adropin in Patients with Alcohol-Induced Liver Cirrhosis

Abstract: Introduction: Liver cirrhosis develops in about 10% of alcohol abusers. To date, a number of cells and cytokines have been identified, which are involved in induction of liver fibrotic processes. Nevertheless, the pathogenesis of liver cirrhosis has not been fully elucidated. The aim of the present study was to determine serum concentrations of afamin and adropin in patients with alcoholic liver cirrhosis and to define their correlation with the stage of disease. Materials and methods: The study included 99 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Although liver is the main source of circulating afamin, there are no functional studies on afamin using human or animal liver cell models. Several publications have reported decreased afamin blood concentrations associated with severe alcoholic liver cirrhosis ( 18 ) and with liver cancer ( 27 , 28 ). In our study, we found a strong positive association between serum afamin and hepatic lipid content, which we observed in two independent study populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although liver is the main source of circulating afamin, there are no functional studies on afamin using human or animal liver cell models. Several publications have reported decreased afamin blood concentrations associated with severe alcoholic liver cirrhosis ( 18 ) and with liver cancer ( 27 , 28 ). In our study, we found a strong positive association between serum afamin and hepatic lipid content, which we observed in two independent study populations.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive hepatic lipid accumulation is associated with non-alcoholic fatty liver disease, hepatic insulin resistance and, increased risk of T2D. However, severe alcoholic liver cirrhosis is associated with a decline in serum afamin, perhaps due to impaired hepatic synthesis ( 18 ). Evidence evaluating a possible role of afamin as a marker of hepatic lipid accumulation and liver disease in a context of obesity and type 2 diabetes is not available.…”
Section: Introductionmentioning
confidence: 99%